Probing long-distance regulatory interactions in the Drosophila melanogaster bithorax complex using Dam identification. - Cleard, F.; Moshkin, Y.; Karch, F.; Maeda, R.K. (Nature Genetics, 2006)
A cis-regulatory region of nearly 300 kb controls the expression of the three bithorax complex (BX-C) homeotic genes: Ubx, abd-A and Abd-B. Interspersed between the numerous enhancers and silencers within the complex are elements called domain boundaries. Recently, many pieces of evidence have suggested that boundaries function to create autonomous domains by interacting among themselves and forming chromatin loops. In order to test this hypothesis, we used Dam identification to probe for interactions between the Fab-7 boundary and other regions in the BX-C. We were surprised to find that the targeting of Dam methyltransferase (Dam) to the Fab-7 boundary results in a strong methylation signal at the Abd-Bm promoter, approximately 35 kb away. Moreover, this methylation pattern is found primarily in the tissues where Abd-B is not expressed and requires an intact Fab-7 boundary. Overall, our work provides the first documented example of a dynamic, long-distance physical interaction between distal regulatory elements within a living, multicellular organism.